1987
DOI: 10.1111/j.1399-0004.1987.tb02831.x
|View full text |Cite
|
Sign up to set email alerts
|

Centric fission, centromere‐telomere fusion and isochromosome formation: a possible origin of a de novo 12p trisomy

Abstract: A 5‐month‐old girl had a typical 12p trisomy syndrome due to a monocentric i(12p) present in a 46‐chromosome complement that also included the translocation of all 12q onto the 8p telomere; i.e., her complex karyotype could be written as 46.XX, – 8,–12,+ der(8),t(8;12)(p23.3;cen), + i(12p). The present concurrence of a whole‐arm q translocation and an i(p) for a single chromocome, along with six previous similar instances involving chromosomes 4, 5 and 9, suggests the following origin for such a special rearra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Constitutional jumping translocations are very rare, and only 7 cases to date have involved concurrent isochromosomes of one arm and translocations of the other [20-26]. The present case is unique, in that it exhibited concurrence of i(Yp) and jumping translocation of Yq as a result of fusion to the telomeres of chromosomes 12q and 17q.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Constitutional jumping translocations are very rare, and only 7 cases to date have involved concurrent isochromosomes of one arm and translocations of the other [20-26]. The present case is unique, in that it exhibited concurrence of i(Yp) and jumping translocation of Yq as a result of fusion to the telomeres of chromosomes 12q and 17q.…”
Section: Discussionmentioning
confidence: 70%
“…Seven instances of concurrent isochromosome of the short arm, i(Yp), and translocation of the long arm of a single chromosome onto a telomere of a nonhomologous chromosome have been described [20-26]. Concolino and colleagues suggested that alpha-satellite fission of the chromosome can result in an isochromosome of the short arm and deletion of the long arm [27].…”
Section: Introductionmentioning
confidence: 99%
“…Our case is the first centric fission of chromosome 12 giving rise to two whole arm telocentric chromosomes (12p and 12q) and leading to a child with a pure and complete trisomy 12p syndrome. Actually, our case is most similar to a couple of trisomy 12p instances: a girl with a 46, XX,þder (8)t(8;12)(p23.3;cen),þi(12p) complement in which the alphoid DNA of the centric fission chromosome was asymmetrically divided among the i(12p) and the derivative [Rivera et al, 1987[Rivera et al, , 1999, and a boy with a 47,XY,-12,þ12q,þpsu idic(12p) karyotype [Plaja et al, 1998]. …”
Section: Discussionmentioning
confidence: 85%
“…De novo cases are due to diverse rearrangements such as free and mosaic chromosome 12p fragments [Kondo et al, 1979;Guerrini et al, 1990;Karki and Walters, 1990;el-Shanti et al, 1997], intrachromosomal duplications [Tayel et al, 1989;Pfeiffer et al, 1992;Leana-Cox et al, 1993;Zelante et al, 1994;Rauch et al, 1996;Tekin et al, 2001;Zumkeller et al, 2004;Tsai et al, 2005;Kim et al, 2006], and extra satellited derivatives including 12p and an acrocentric's short arm [Dallapiccola et al, 1980;Ray et al, 1985;Allen et al, 1996]. Rivera et al [1987] reported a unique case with de novo trisomy 12p who had a 12q whole arm translocation onto the 8p telomere and an isochromosome 12p.…”
Section: Introductionmentioning
confidence: 99%
“…In four patients, a malsegregation type 3 : 1 of a parental balanced reciprocal translocation led to a dup( 12p) as well as to partial duplications of 5p, 8q, 8p, and 18p (AndrC et al 1976, Nielsen et al 1977, Savary et al 1977, Serville et al 1978. Only 12 cases were de novo events, two of them caused by isochromosome formation of the entire short arm (Rivera et al 1987, Marques-de Faria et al 1989, one by an additional del( 12)(qll) chromosome as a mosaic with a normal cell line (Kondo et al 1979), four by translocation of 12p onto the short arm of an acrocentric or an undefined chromosome (Dallapiccola et al 1980, Ray et al 1985, Guerrini et al 1990, Allen et al 1996. three by direct tandem duplication of 12pter-p12.1 rsp.pl3.1, the second as a mosaic (Tayel et al 1989, Leana-Cox et al 1993, Rauch et al 1996, and a further two by inverted tandem duplication of 12p13.3+p11.2 rsp.pI3.2, the latter as a mosaic (Pfeiffer et al 1992, Rauch et al 1996.…”
Section: Discussionmentioning
confidence: 99%